Elemen ‘Ulum Al-Quran dalam manuskrip Quran bergantung makna Melayu oleh Shaykh Muhammad Idris Al-Marbawi - Mohd, Nor Syamimi; Fadzil, Ammar; Ahmad, Nadzrah (PIMM Experts Sdn Bhd, 2022)
The fields of knowledge known as ‘ulum al-Quran (science of the Quran) and Quranic interpretation are closely related and mutually beneficial. Most authors of tafsir books begin their interpretation by describing the ‘ulum al-Quran as a muqaddimah (introduction) and then debate various interpretations. Al-Tabari, Ibn 'Athiyyah, and Ibn Hayyan all engaged in this. However, the exegetes of Quranic interpretations have different tendencies to debate ‘ulum al-Quran in their respective books, whether discussed in depth or not or not. Thus, the purpose of this research is to analyse the extent to which Shaykh Mohamed Idris al-Marbawi debated the element of the science of the Quran in his scribble titled Quran Bergantung Makna Melayu. The method of content analysis was employed to design this qualitative research. Document analysis is used to collect data, and the data obtained is descriptively analysed. The findings indicate that Shaykh al-Marbawi pays only cursory attention to the debate over the 'ulum al-Quran. The debate covered topics such as makki and madani, asbab nuzul, and nasikh mansukh. The implications of the study show that the Quran Bergantung Makna Melayu by Shaykh al-Marbawi is an authentic book of interpretation and is in line with the current needs of the society which requires a simple and understandable interpretation.